2005
DOI: 10.1038/ni1237
|View full text |Cite
|
Sign up to set email alerts
|

The Jak-STAT signaling pathway is required but not sufficient for the antiviral response of drosophila

Abstract: The response of drosophila to bacterial and fungal infections involves two signaling pathways, Toll and Imd, which both activate members of the transcription factor NF-kappaB family. Here we have studied the global transcriptional response of flies to infection with drosophila C virus. Viral infection induced a set of genes distinct from those regulated by the Toll or Imd pathways and triggered a signal transducer and activator of transcription (STAT) DNA-binding activity. Genetic experiments showed that the J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
591
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 577 publications
(635 citation statements)
references
References 50 publications
25
591
2
5
Order By: Relevance
“…Another pathway that has known signaling roles in innate immunity and in particular in anti-viral immunity is the JAK/Stat pathway [16][17][18]. Three large-scale RNAi screens have been performed, which probed the IMD signaling pathway in response to peptidoglycan [19][20][21] (Table 1).…”
Section: Anti-microbial Signaling Screensmentioning
confidence: 99%
“…Another pathway that has known signaling roles in innate immunity and in particular in anti-viral immunity is the JAK/Stat pathway [16][17][18]. Three large-scale RNAi screens have been performed, which probed the IMD signaling pathway in response to peptidoglycan [19][20][21] (Table 1).…”
Section: Anti-microbial Signaling Screensmentioning
confidence: 99%
“…21,22 Safia Deddouche (Jean-Luc Imler's lab, University of Strasbourg, in collaboration with several others) reported on the gene Vago, which is induced in the fat body after viral infection in a JAK-STAT independent manner, and suppresses proliferation of Drosophila C Virus (DCV). Deddouche and colleagues showed that the Flock House Virus protein B2, which interferes with RNAi through Dicer-2, suppresses induction of Vago.…”
Section: Other Immune Mechanismsmentioning
confidence: 99%
“…However, a number of viruses, including DCV, encode suppressors which inhibit this response (van Rij et al, 2006). Microarrays and proteomics have been used to identify genes and proteins that are upregulated in response to DCV infection in Drosophila (Dostert et al, 2005;Roxstrom-Lindquist et al, 2004;Sabatier et al, 2003). A number of genes have been found to be upregulated in response to DCV infection and one protein has been identified as being induced in the haemolymph of DCV-infected Drosophila (Sabatier et al, 2003).…”
mentioning
confidence: 99%
“…A number of genes have been found to be upregulated in response to DCV infection and one protein has been identified as being induced in the haemolymph of DCV-infected Drosophila (Sabatier et al, 2003). Dostert et al (2005) identified 140 genes that were upregulated in adult Drosophila 24 and 48 h post injection with DCV. Two thirds of these genes were not upregulated in response to bacterial or fungal infections (Dostert et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation